The normativity of rationality: a defense - Levy, Y (2013)
Rationality is very widely regarded as a normative notion, which underwrites various everyday normative practices of evaluation, criticism, and advice. When some agent behaves irrationally, she is likely to be critically evaluated, and advised to change her ways. Such practices seem to presuppose that agents ought to behave as rationality requires. But some philosophers question this thought. They argue that at least some requirements of rationality cannot be ones that we ought to comply with. This thesis aims to dispel such sceptical doubts over the normativity of rationality; it defends the idea that the requirements of rationality are indeed normative, in the sense that if one is rationally required to F, one ought to F because rationality requires one to F. The normativity of three requirements of practical rationality in particular is the main target for defense in the following pages. They are: [ENKRASIA] Rationality requires of A that, if A believes she ought to F, then A intends to F. [MEANS-ENDS] Rationality requires of A that, if A intends to E, and believes that she will not E unless she intends to M, then A intends to M. [INTENTION CONSISTENCY] Rationality requires of A that, if A intends to F, and believes that she cannot both F and G, then A does not intend to G. After presenting some of the grounds for scepticism about the normativity of these three requirements in chapter 1, the thesis goes on in chapters 2 & 3 to critically examine several different accounts of why rationality is normative, concluding that they are all unsuccessful; a novel account is called for. An account of this kind is offered over the course of the two following chapters, 4 & 5. Each requirement is shown to be constituted by a certain kind of ought, while at the same time corresponding to a rule of correct reasoning. Chapter 6 is devoted to answering an objection to that account, according to which the rules of reasoning are given by permissions rather than requirements. Chapter 7 offers a digression into a related issue in action theory: it unfavorably explores the idea that reasoning is a factor that can be used to analyse not only rational action, but also intentional action more broadly; the chapter suggests that treating intentional action as irreducible is the more fruitful approach. Finally, chapter 8 summarizes the main conclusions of the thesis and comments on some remaining questions.